Decolonising forensic odontology in Sub-Saharan Africa - Salma Kabbashi; Keane Bailie; Susan Chandler; Manogari Chetty (Forensic Science International: Synergy, 2025)
Forensic odontology plays a vital role in human identification, age estimation, and legal investigations. However, in Sub-Saharan Africa, the field has developed within a framework shaped by colonial histories, Western methodologies, and systemic underinvestment in local capacity. This article critically examines the need to decolonise forensic odontology in the region, proposing a comprehensive reform agenda grounded in four intersecting domains: historical legacies, indigenous knowledge integration, ethical considerations, and policy reform. It highlights how colonial-era forensic practices continue to influence current protocols and legal standards, often to the detriment of scientific accuracy and justice. By recognising and incorporating traditional dental knowledge, such as ritual dental modifications and community oral histories, the field can be enriched and made more contextually relevant. Ethical challenges surrounding data sovereignty, informed consent, cultural sensitivity, and the use of contested techniques are addressed, with recommendations for more equitable and transparent forensic practices. Policy reforms are proposed to institutionalise forensic odontology through education, infrastructure development, legal recognition, and collaborative networks. The article argues that decolonisation is not a rejection of global science but a reorientation toward context-appropriate, ethically grounded, and locally led forensic systems. Through these reforms, Sub-Saharan Africa can build a forensic odontology discipline that is scientifically robust, culturally responsive, and capable of delivering justice and dignity to affected communities.